Diagnostic performance of contrast-enhanced spectral mammography: Systematic review and meta-analysis. (August 2016) - Tagliafico, Alberto Stefano; Bignotti, Bianca; Rossi, Federica; Signori, Alessio; Sormani, Maria Pia; Valdora, Francesca; Calabrese, Massimo; Houssami, Nehmat
Abstract: Purpose: To estimate sensitivity and specificity of CESM for breast cancer diagnosis. Methods: Systematic review and meta-analysis of the accuracy of CESM in finding breast cancer in highly selected women. We estimated summary receiver operating characteristic curves, sensitivity and specificity according to quality criteria with QUADAS-2. Results: Six hundred four studies were retrieved, 8 of these reporting on 920 patients with 994 lesions, were eligible for inclusion. Estimated sensitivity from all studies was: 0.98 (95% CI: 0.96–1.00). Specificity was estimated from six studies reporting raw data: 0.58 (95% CI: 0.38–0.77). The majority of studies were scored as at high risk of bias due to the very selected populations. Conclusion: CESM has a high sensitivity but very low specificity. The source studies were based on highly selected case series and prone to selection bias. High-quality studies are required to assess the accuracy of CESM in unselected cases. Highlights: CESM has a high sensitivity with capability of detecting vascularized malignant lesions of the breast but very low specificity. The studies on CESM were based on highly selected case series and prone to selection bias, evident by both the quality appraisal and the extremely high prevalence of breast cancer across studies. High-quality studies are required to assess the accuracy of CESM in unselected cases. If CESM is going to be used in screening, or if CESM will be considered as a potential alternative to diagnostic MRI. There is limited evidence that CESM could replace or complement the current imaging modalities in breast cancer diagnosis.